SYNTHETIC POLYMERS ON WATER RETENTION AND PORE DISTRIBUITION IN A CLAYEY LATOSOL - Benevenute, Pedro Antônio Namorato; Passos, Lucas Ademir Carvalho; Melo, Laura Beatriz Batista de Melo Batista de; Silva, Érika Andressa da; Oliveira, Geraldo César de (Scientia Agraria, 2017)
The use of polymers is growing at the agricultural area, however their effects on soil porosity have been little studied. The objective of this article is to analyze the effects of applied synthetic polymers on soil porosity and water retention of a Dystroferric red Latosol. This study was conducted on undisturbed samples collected at a depth of 0.05m in a Latosol beneath native forest. The samples were saturated with distilled water and polymers HyC, HyA, HyB diluted in water according to use recommendations for coffee plantations. These samples were then submitted to matric potentials of -2, -4, -6 and -10 kPa in the suction units and -33, -100, -500 and -1500 kPa in a Richards extractor. Water retention curves were moldeled and pore size distribution estimates calculated. The data were subjected to variance analysis and the averages were compared using the Scott-knott test to a level of 5%. There was a reduction of the pore volume of size class larger than 145µm when the soil was saturated with HyA and HyB polymers. On one hand the HyB polymer promoted a reduction in the pore volume in the intermediate classes (2.9-0.6; 0,.-0.2 µm), that were responsible for providing water to the plants. On the other hand the HyC polymer promoted an increase in the soil water retention.